Respuesta :

Answer:

B.  √5

Step-by-step explanation:

Given:

[tex]K=\sqrt{9-4\sqrt{5}}[/tex]

[tex]\implies K+2=\sqrt{9-4\sqrt{5}}+2[/tex]

Rewrite 9 as 5 + 4:

[tex]= \sqrt{5-4\sqrt{5}+4}+2[/tex]

Rewrite 5 as (√5)², 4 as 2² and 4√5 as 2 · 2√5:

[tex]= \sqrt{(\sqrt{5})^2-2 \cdot 2\sqrt{5}+2^2}+2[/tex]

Apply the perfect square formula  [tex]a^2-2ab+b^2=(a-b)^2[/tex]:

[tex]=\sqrt{(\sqrt{5}-2)^2}+2[/tex]

Apply radical rule  [tex]\sqrt{a^2}=a[/tex]

[tex]=\sqrt{5}-2+2[/tex]

Simplify:

[tex]=\sqrt{5}[/tex]